APLIKASI PLANT GROWTH PROMOTING RHIZOBACTERIA (PGPR) TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Julianus Jeksen (AGRICA, 2014)
This study aims at finding out the PGPR dose on the growth of cocoa seed and investigating the optimum dose of PGPR that can grow cocoa seed. A random block design was employed in this study with the treatment of 7,5 ml PGPR seed-1 (PG 1), and PGPR 15 ml PGPR seed-1 (PG 2), the PGPR dose of 30 ml PGPR seed-1 (PG 3), and PGPR 45 ml PGPR seed-1 (PG 4). The result of this research indicates that the treatment of PGPR dose has an apparent influence on the growth of the cocoa seed. The better cocoa seed growth is that the plant height improves to 5,26%, leaves a total number of 5,64%, leaves width of 8,36%, the diameter of stem increases to 12,00% mm, the weight of wet fresh stover plant-1 rises to7,69% and dry weight of stover plant-1increases to 10,71%. The optimum dose of PGPR for cocoa seeding is 45 ml PGPR seed-1.